Design of Customer Satisfaction Application at BCA Kcp Rengasdengklok Using C.45 Algorithm Method (Buana Information Technology and Computer Sciences (BIT and CS), 2022)
Bank BCA always improves service quality by the slogan "Always By Your Side". The assessment consists of 4 attributes (time, accuracy, focus, and satisfaction). Each attribute has a weighted value of 1 (very dissatisfied) to 5 (very satisfied). The assessment is still done manually (using paper), therefore the authors in this study used the C.45 algorithm with 3 tests carried out to produce a classification obtained that the accuracy value reached 88.75% with an AUC value of 0.744 and testing on the application that was made resulted in 0.722. It can be concluded that service assessment at BCA KCP Rengasdengklok belongs to a fairly good classification group because its AUC value is between 0.70-0.80.